THE EFFECT OF PSYCHOEDUCATION ON THE INCIDENT OF POSTPARTUM BLUES IN BANJARSARI VILLAGE, BANJARSARI DISTRICT, SURAKARTA - Yunanto, Enyk; Yunia Renny Andhikatyas; Migita Vidia Amita (Universitas STRADA Indonesia, 2023)
Background: Postpartum blues affect many mothers in Asia, 15-85%. This study will explore the impact of psychoeducation on postpartum blues in women after giving birth Methods: This study was a quasi-experimental design with a pre-and post-test approach for a group of postpartum mothers selected through purposive sampling. To measure the incidence of postpartum blues using EPDS questionnaire and the Wilcoxon test were used for data analysis. Result: The average pre-test score was 9.92, which categorized at risk for postpartum blues, the post-test score was 7.28, categorized as not at risk for postpartum blues. Analysis: Wilcoxon test results obtained z value = -4.449 and p-value = 0.000 this means that there is an effect of providing psychoeducation on the incidence of postpartum blues Conclusion: Providing therapy in the form of psychoeducation has been proven to be effective in reducing the risk of postpartum blues.